RACISM IN 42 MOVIE DIRECTED BY BRIAN HELGELAND - Yuyun Dwi Laksmiati; Bejo Sutrisno; Budi Rachmawati (STIBA IEC JAKARTA, 2022)
This Thesis is an attempt to find the racism that occurred by the man character in 42 movie. There are 3 problems of the study: (1) What are the factors causing the racism in 42 movie? (2) How to determine the racism in 42 movie by Brian Helgeland? (3) What are the effects of racism in 42 movie by Brian Helgeland?. A qualitative methods used to explain about Racism in 42 movie directed by Brian Helgeland. The data were collected from websites, references books, some articles, and the original movie. The writer watched the movie many times to get the point of story in this movie. Put the dialogues or the conversation that related with the main title in this paper to analyze the data. The results of this research indicates: first, the factor of racism are from culture and America history, second, determining racism by selecting the racism action that occurred between white and black ,the third effect of racism upon the offender and upon the victim, and the last moral message from racism action in 42 movie